ANALYSIS OF THE MUTUAL TRADE BETWEEN THE EU AND INDONESIA - Peter Bielik; Luboš Smutka; Elena Horská; Mansoor Maitah (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Mutual trade between EU countries and Indonesia is a bilateral commodity trade flow exceeding 17 billion Euros. Analysis of the trade between the two entities is an important contribution leading to the definition of the significance that the ongoing cooperation between the EU and Indonesia has. EU is for Indonesia very important trading partner, for EU is Indonesia a strategic political partner. The bilateral trade is currently greatly benefiting Indonesia, however, this market has a potential for EU due to the fact, that it is one of the most populous country in the Asian region and the in world in general. The trade exchange is based on export and import of most basic aggregate commodities; while between the two partners exist significant differences in terms of available comparative advantages. A specificity of the mutual trade is the limited territorial structure of this exchange, as the main volume of transactions is realized between Indonesia and only a few EU countries.   Keywords: EU, Indonesia, mutual, foreign trade, commodity, territory, structure, analysis, competitiveness